Makna Perfeksionisme pada Mahasiswa Berkepribadian Melankolis dalam Konteks Pendidikan Tinggi: Studi Fenomenologi - Sri Nurhayati Selian; Putri Balqis (STAB Kertarajasa, 2026)
This study aims to understand the meaning of perfectionism in individuals with melancholic personalities in the context of higher education. The study used a qualitative approach with phenomenological methods to explore the subjective experiences of participants. Research subjects were selected using a purposive sampling technique with the criteria of individuals with melancholic personality tendencies and currently studying at university. Data were collected through in-depth semi-structured interviews, observation, and documentation, then analyzed using thematic analysis techniques. The results show that perfectionism is interpreted as an internal drive to achieve high standards while also being a source of psychological stress. Perfectionism manifests itself in the form of a desire to produce the best results, repeated revisions, and sensitivity to academic assessments. On the other hand, perfectionism also has negative impacts such as overthinking, mental fatigue, and self-dissatisfaction in the learning process. These findings indicate that perfectionism in melancholic individuals in higher education environments is complex, serving as both motivation and a source of stress. Therefore, self-management skills and support from educators and guidance and counseling services in higher education are needed so that perfectionism can become a constructive drive without disrupting students' psychological well-being.